Morphological Evolution of an Intertidal Area Following a Set-Back Scheme: A Case Study From the Perkpolder Basin (Netherlands) - Brunetta, Riccardo; de Paiva, João Salvador; Ciavola, Paolo (Frontiers in Earth Science, 2019)
In the present context of sea-level rise, the reconstruction of previously reclaimed intertidal areas represents an opportunity to build dynamic coastal defences to decrease flooding under storm conditions by the dissipation of wave and surge energy across the vegetated domain. In Europe, this approach started in the late 1990s along the coast of eastern and southern England, but it is becoming common to many European countries around the North Sea margin. The process of salt-marsh restoration normally develops around the opening or removal of flood protection structures and gradual flooding of the hinterland. If the intertidal zone starts to experience vertical accretion, vegetation will colonize the area and a saltmarsh will develop. This paper presents the morphological evolution and sediment distribution in the Perkpolder basin, SW Netherlands (NL), following the conversion of a reclaimed area into a tidal flat, after the opening of an inlet in the flood defence structures in June 2015. The main focus of this study is the description of the evolution of the tidal flat since the opening of the inlet and the identification of spatio-temporal conditions for the evolution of a salt marsh. To reach this objective, several topographic surveys were undertaken, together with sediment surface sampling. Sedimentation rates at fixed sampling stations were assessed during the transition between neap and spring tides over a period of 1 month and 2 weeks. The morphological analysis of the inlet evolution proved that 6–8 months after the opening the inlet reached an equilibrium state. The average accretion rate across the whole study area was about 6–7 cm per year–1. The average deposited sediment was about 100 g per m–2 per day. Considering the sedimentation rates in the most elevated regions, 80–110 cm above NAP (Normaal Amsterdams Peil), and assuming that the sedimentation rate will remain constant in time, the conditions for the on-set of salt-marsh formation will not be reached before 8–10 years. Projections indicate that the area located at +50 cm above NAP will not become a mature marsh before 50 years.